Neurocognitive impairment in patients with bipolar disorder: Comparison between first episode and multiple episodes - Rashmin Achalia; Garimaa Achalia; Sudhir Chaudhary; Mahesh Chopade; Varsha Kaginalkar; Abhijit Sable; Arpitha Jacob; Ganesan Venkatasubramanian; Naren P Rao (Annals of Indian Psychiatry, 2020)
Background: Several lines of evidence in the last few years have suggested the critical role of neurocognitive deficits in functional recovery of patients with bipolar disorder (BD). However, whether these deficits are static or progressive with the course of the illness is still debated. Surprisingly, the effect of multiple episodes on neurocognitive deficits in BD is rarely examined in first-episode Indian patients. Hence, in this study, we aimed to examine the difference between first episode mania and BD patients with multiple episodes. Methodology: Thirty patients with the Diagnostic and Statistical Manual of Mental Disorders-IV BD-I (13 with first-episode mania; 17 with multiple episodes) and 30 age- and sex-matched healthy volunteers (HV) were recruited in the study. Clinical severity was assessed using structured rating scales. All patients performed tests to measure executive functions, namely continuous performance test, Stroop color word interference test, and Wisconsin Card Sorting Test. Differences between groups were examined using the analysis of covariance with age and sex as covariates with Bonferroni post hoc analysis. Results: There was a significant difference between groups on the performance of all three tests with patients performing poorer than HV. While the HV differed from both first episode mania and BD with multiple episodes, there was no difference between the two patient subgroups. There was no significant correlation between clinical variables and scores on neurocognitive tests. Conclusions: The study findings, with respect to cognitive function, supports neurodevelopmental than neurodegenerative hypothesis. Findings indicate the need to assess cognitive functions in all patients with BD including first episode BD.